Analisis Faktor-Faktor Penghambat Pengajuan Klaim BPJS Rawat Inap di Rumah Sakit Umum Haji Medan - Khairunnisa Azzahra; Fauzi Arif Lubis; Wahyu Syarvina (Universitas Muhammadiyah Enrekang, 2023)
This study aims to determine the Analysis of Factors - Factors Inhibiting Filing of BPJS Claims for Hospitalization at Medan Hajj Hospital. This research uses a descriptive method with a qualitative approach. The results of this study indicate that the inhibiting factors for submitting inpatient BPJS claims at Medan Haji General Hospital because the terms and conditions for claim administration are always changing make many claim files returned by the verifier, so the process becomes slow. Data collection using interviews and observation of inpatient claim files. The results of the study showed that patients did not understand or lack knowledge of BPJS patients regarding the BPJS inpatient registration procedure and results. In 2018 BPJS inpatient claims amounted to 6,799 with a total bill of 31,953,602,522. In 2019 BPJS claims for inpatients totaled 157 with a total bill of 7,348,427,289 and in 2019 inpatients experienced pending failure as many as 224 patients with a total bill of 1,911,164,300. In 2020 BPJS claims for inpatients amounted to 4,319 with a total bill of 21,341,474,918. In 2021 BPJS claims for inpatients amount to 498 with a total bill of 3,127,099,000.